THE RELATIONSHIP BETWEEN PRINCIPAL LEADERSHIP STYLE AND JOB SATISFACTION ON TEACHERS’ WORK DISCIPLINE - Awang Darmawan Putra; Alfia Azzuhra (Universitas Negeri Surabaya, 2025)
The development of educational institutions is highly dependent on the capacity and productivity of educators within those institutions. With professional human resource management arrangements, it is hoped that educators and education personnel can work well. The school's human resources include the principal, teachers, students, staff, and the community. This study aims to measure the correlation between the principal's leadership style and job satisfaction with teacher work discipline, a study conducted at four private junior high schools in Bogor Regency. The research method uses descriptive and verification analysis with an explanatory survey of 80 teachers from the four schools. The research results show that the total correlation between leadership style, job satisfaction, and teacher work discipline is 0.230 or about 23.0%. Leadership style has a greater influence on subordinate work discipline than job satisfaction, both directly and indirectly. Therefore, it is important to make efforts to improve leadership styles in order to increase teacher work discipline and to improve job satisfaction in order to increase teacher work discipline.